Antioxidant agents against trichothecenes: new hints for oxidative stress treatment - Wu, Qinghua; Wang, Xu; Nepovimova, Eugenie; Wang, Yun; Yang, Hualin; Li, Li; Zhang, Xiujuan; Kuca, Kamil (Oncotarget, 2017)
Trichothecenes are a group of mycotoxins mainly produced by fungi of genus Fusarium. Due to high toxicity and widespread dissemination, T-2 toxin and deoxynivalenol (DON) are considered to be the most important compounds of this class. Trichothecenes generate free radicals, including reactive oxygen species (ROS), which induce lipid peroxidation, decrease levels of antioxidant enzymes, and ultimately lead to apoptosis. Consequently, oxidative stress is an active area of research on the toxic mechanisms of trichothecenes, and identification of antioxidant agents that could be used against trichothecenes is crucial for human health. Numerous natural compounds have been analyzed and have shown to function very effectively as antioxidants against trichothecenes. In this review, we summarize the molecular mechanisms underlying oxidative stress induced by these compounds, and discuss current knowledge regarding such antioxidant agents as vitamins, quercetin, selenium, glucomannan, nucleotides, antimicrobial peptides, bacteria, polyunsaturated fatty acids, oligosaccharides, and plant extracts. These products inhibit trichothecene-induced oxidative stress by (1) inhibiting ROS generation and induced DNA damage and lipid peroxidation; (2) increasing antioxidant enzyme activity; (3) blocking the MAPK and NF-κB signaling pathways; (4) inhibiting caspase activity and apoptosis; (5) protecting mitochondria; and (6) regulating anti-inflammatory actions. Finally, we summarize some decontamination methods, including bacterial and yeast biotransformation and degradation, as well as mycotoxin-binding agents. This review provides a comprehensive overview of antioxidant agents against trichothecenes and casts new light on the attenuation of oxidative stress.
Keywords: T-2 toxin; trichothecenes; deoxynivalenol; antioxidant agents; oxidative stress